1993
DOI: 10.1007/bf01067426
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci (QTL) applications to substances of abuse: Physical dependence studies with nitrous oxide and ethanol in BXD mice

Abstract: Recombinant inbred (RI) mouse strains were developed primarily as a tool to detect and provisionally map major gene loci--those with effects large enough to cause a bimodal distribution in the trait of interest. This implied that progress toward gene mapping was possible only for gene loci accounting for at least half of the genetic variance. More recently, QTL (quantitative trait loci) approaches have been advanced that do not require bimodal distributions and are thus applicable to a much wider range of phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 42 publications
4
69
0
Order By: Relevance
“…Although several groups have used various RI series for the provisional mapping of QTLs influencing several ethanol related responses (McClearn et al 1992;Belknap et al 1993;Crabbe et al 1994b;Rodriguez et al 1995;Markel et al 1996a), our F2 results strongly encourage confirmation or disproof of provisional QTLs from RI-mapping experiments using large F2 stocks.…”
Section: Discussionmentioning
confidence: 53%
“…Although several groups have used various RI series for the provisional mapping of QTLs influencing several ethanol related responses (McClearn et al 1992;Belknap et al 1993;Crabbe et al 1994b;Rodriguez et al 1995;Markel et al 1996a), our F2 results strongly encourage confirmation or disproof of provisional QTLs from RI-mapping experiments using large F2 stocks.…”
Section: Discussionmentioning
confidence: 53%
“…QTLs obtained in one set of RIs can be further confirmed in other sets of RIs, in F2 or backcross progeny of the parental strains (from which RIs are derived), or in their congenic strains (see examples in Belknap et al 1992a;Crabbe et al 1994).…”
Section: Introductionmentioning
confidence: 86%
“…We first mapped expression changes identified in our studies versus chromosomal regions assigned to confirmed QTLs for acute locomotor responses to ethanol, acute ethanol withdrawal, or ethanol preference drinking (for review, see Belknap et al, 1993). Other ethanol behavioral QTLs might also involve genes identified in these studies, but we focused on these behaviors for reasons noted above.…”
Section: Correlation Of Expression Profiling With Qtl Studies On Ethamentioning
confidence: 99%